1 Задание
(a+4)² = а² + 8а + 16
(3a-6)² = 9а² - 36а + 36
(7y-3)(7y+3) = 49у² - 9
(8y+7d)(8y-7d) = 64y² - 49d²
2 Задание
(d-6)² - (36 + 3d) = d² - 12d + 36 - 36 - 3d = d² - 15d = d(d - 15)
3 Задание
(8 - y)² - y(y + 5,5) = 42,5
64 - 16y + y² - y² - 5,5y = 42,5
-21,5y = -21,5
y = 1
4 Задание
p² - 16 = (p - 4)(p + 4)
81t²-18ts+s² = (9t - s)² = (9t - s)(9t - s)
5 Задание
16d²-g²-9b⁸ = (4d - g + 3b⁴)(4d - g - 3b⁴)
49b² - (b+10)² = (7b - b - 10)(7b - b + 10) = (6b - 10)(6b + 10)
64w³+n⁹
6 Задание
(d² - 4f)(4f + d²) = d⁴ - 16f²
(t⁴-7t)² = t⁸ - 14t⁵ + 49t²
(t-a)²(t+a)² = t⁴ - 4t²a² + a⁴
Объяснение: b₁, b₂, b₃, b₄ - ?
b₃-b₁ =12;
b₅-b₃ =48;
b₃=b₁×q²; b₅=b₁×q⁴;
Составим систему уравнений:
b₃-b₁ =12;b₅ - b₃ =48; b₁×q²-b₁ =12;2. b₁×q⁴ - b₁×q²=48;
1. b₁×(q²-1)=12;
2. b₁×(q⁴-q²)=48;
Разделим 2-е уравнение на 1 : (b₁×(q⁴-q²))/(b₁×(q²-1)) =(48/12);
(q²×(q²-1))/(q²-1) =4;
q²=4; → q=±√4=±2;
Если q=2, то b₁×(q²-1)=12; → b₁=12/(q²-1) =12/(2²-1) =12/3=4;
b₂=b₁*q=4*2=8; b₃=b₁*q²=4*2²=4*8=16; b₄=b₁*q³=4*2³=4*8=32.
Если q=-2, то b₁=12/(q²-1) =12/((-2)²-1) =12/3=4; b₂=b₁*q=4*(-2)=-8;
b₃=b₁*q²=4*(-2)²=16; b₄=b₁*q³=4*(-2)³=4*(-8)=-32.
ответ: при q=2, b₁b₄ → (4;8;16;32);
при q= -2, b₁b₄ → (4;(-8);16;(-32)).